2013
DOI: 10.1111/acem.12146
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Nonfatal Bicycle Injuries Presenting to United States Emergency Departments, 2001–2008

Abstract: Objectives: The purpose of this study was to describe the epidemiology of bicycle-related injuries presenting to United States emergency departments (EDs). Methods:The National Electronic Injury Surveillance System All Injury Program (NEISS-AIP) database was used to derive national, weighted estimates of nonfatal ED visits for bicycle-related injuries by patient age, sex, diagnosis, injured body part, locale of incident, traffic-relatedness of incident, and month of incident.Results: Males accounted for 73% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 22 publications
6
42
0
2
Order By: Relevance
“…Notable subtypes of this type of trauma are incidents involving bicycles or motorcycles, which are represented at a significant percentage as etiological agents. In our sample, these specific agents accounted for over 20% of reported causes of facial trauma, corroborating the findings of other studies [13,[17][18][19]21,22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notable subtypes of this type of trauma are incidents involving bicycles or motorcycles, which are represented at a significant percentage as etiological agents. In our sample, these specific agents accounted for over 20% of reported causes of facial trauma, corroborating the findings of other studies [13,[17][18][19]21,22].…”
Section: Discussionsupporting
confidence: 92%
“…Among these 202 cases, of the 154 patients involved in a motorcycle crash, only 20 were women; of the 48 bicycle accidents, only four involved women (Table 4). A study [22] of the epidemiology of bicycle crash in the United States between 2001 and 2008 found that 73% of cases involved men. Conversely, another study [19] showed that Dutch women accounted for nearly half of all cases of facial fractures secondary to bicycle accidents; in Italy, 26 of 105 victims were women.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the NEISS's accuracy in identifying injuries. 3,4,11 The NEISS database is updated daily and allows estimation of the epidemiology of injury-related ED visits. Data regarding tricycle (product code: 1301) injuries among children ,18 years of age were retrospectively analyzed from calendar years 2012 to 2013 using the NEISS database.…”
Section: Data Sourcementioning
confidence: 99%
“…3,4 These measures have had a dramatic impact on bicycle safety. 5 However, little attention has been given to the characteristics of tricycle injuries.…”
mentioning
confidence: 99%
“…Many of these studies focus on just one human-powered vehicle such as bicycles, [2] skateboards, [3,4] roller skates, [5] or scooters. [6][7][8] Each of these studies enhances our understanding of the injury risks associated with a particular type of vehicle but inherently precludes direct comparisons across types of vehicles, particularly since the analyses generally rest on different databases, encompass different time frames, and/or cover different geographic locations.…”
Section: Introductionmentioning
confidence: 99%